Cyber warfare and its impact on international relations: The Zionist entity’s war on Hezbollah as a model (قضايا سياسية, 2025)
Cyber ??warfare is one of the most important wars used in international relations. Its use has developed as a result of the tremendous progress in information and communications technology. This war has gradually become a substitute for traditional warfare. In this study, which is one of the modern studies on cyber warfare, its research problem was defined as the impact of the use of cyber warfare on international relations, using the Israeli cyber war on Hezbollah as a model for that war. This study used the descriptive approach in its research methodology in addition to the power approach in international relations. The study was based on one hypothesis that says: Cyber ??warfare does not have a significant impact on international relations. The study proved the invalidity of this hypothesis, as cyber warfare is of great importance in influencing international relations and even an introduction to comprehensive military wars after its use. The study reached a number of results, the most important of which was that most countries in the world realize the importance of developing modern strategies for wars that subjugate opponents with low material and human costs. It is also impossible to dispense with military force (hard) after using cyber warfare, as hard warfare follows it. This was clear and evident when Israel launched Its cyber attacks on Hezbollah as a prelude to launching a comprehensive military war on the party. The study also concluded that it is important to benefit from technological progress in building modern armies, including cyber power.